Septicemia caused by Pseudomonas aeruginosa: a review - Sayre, James W. (The Turkish Journal of Pediatrics, 1963)
A discussion of the causes, incidence and treatment of Pseudomonas aeruginosa, with emphasis on its relation to antibiotic therapy and predisposing factors. Special attention is focused on Ps. aeruginosa septicemia in burn cases. Preventive measures are suggested as a means of reducing this hospital-acquired infection.